POLITISASI ANGGARAN SEKTOR PUBLIK - Pratiwi, Ratih Nur (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
Researches on the budgetary politics public sector organization seem very few. This research, therefore, attempts to identify, describe, analyses and interpret the budgetary politics public sector. Â Qualitative research come into consideration with naturalistic paradigm to have holistically deep review of problem totally in politics context.Result of research indicate that process budget preparation and determination involves some actors in which each actor has-needed different personal. Some actors do importance and politization of budged for public sector. Local official as agent in preparing budget draft tends to create stipulating of budget harming public. The reasons behind the budgetary politics public sector organization must be (1) the role manager department in process of compilation and stipulating of budget only see requirement of each institution by raising budget (2) bureaucratic procedure, full with political content, (3) At ratification stage, budget committee doesnât consider relevance test, urgent test, cost effectiveness test. But concern with higher politic (4) local parliament as public people proxy doesnât fight for budget for public so politization of budget happened for the sake of functionary.Keyword: The budget political; public sector.